The ebbs and flows of the Catholicism of Czesław Miłosz in social dimension - Breczko, Jacek (Folia Philosophica, 2017)
In this article I deal with Czeslaw Milosz’s relationship to Catholicism in the social dimension. We can see in his position an ambivalence, not only in his life, but also in relation to the civilization and political role of the Church: from the strong acceptance on the historical and civilization level (“radical Catholicism”), to a strong dislike of the unions of Catholicism with the nationalism in various countries, especially in Poland; from sympathy for Catholic modernism, to a strong dislike of some post-Vatican II rulings, which was, to some extent, a legacy of modernism. Moreover, Milosz did not want the Christian religion and the Catholic Church to be used politically (either through the left-wing politics, progressive politics, or nationalist politics), but also feared the dominance of the Church, the theocratic attempts. He did not want to subordinate the political sphere to religion or to subordinate religion to the political sphere. I treat this text as contributing to a more general theme, namely the attitude of Polish intellectuals to Catholicism in the 20th century